Robots don't catch chicken pox - Dadey, Debbie; Jones, Marcia (Marcia Thornton); Gurney, John. (New York : Scholastic, Inc., 2000)
There are some pretty weird grown-ups living in Bailey City. But could the drama teacher directing the class play really be a robot?
"A little Apple paperback."
RL:3
Ages 7-10
600
Accelerated Reader AR
Keywords: Robots -- Juvenile fiction; Schools -- Juvenile fiction